Peran Advokat Dalam Pemenuhan Hak-Hak Korban Tindak Pidana Asusila; Suatu Kajian Terhadap Pengacara Korban - Marbun, Herbet; Irawan, Benny; Yulia, Rena (Universitas Sultan Ageng Tirtayasa, 2024)
There are no regulations regarding advocates in terms of accompanying victims, but so far there have been regulations regarding victims' rights, but the role of advocates is not regulated in detail and is not complete in assisting victims' rights because the role of advocates so far does not function fully for victims but only for suspects. This research aims to determine the role of Advocates in fulfilling victims' rights in the current criminal justice system and the role of Advocates in fulfilling victims' rights in the criminal justice system in the future from the perspective of criminal law reform. This research is a type of normative juridical research with a statutory approach. The role of advocates in fulfilling victims' rights in the criminal justice system. Currently, advocates never participate even though advocates are included in the criminal justice system because in Pasal 54 Undang-Undang No. 8 Tahun 1981 tentang Hukum Acara Pidana (“KUHAP”) It does not regulate the assistance of victims by advocates and also cannot provide legal assistance to victims because the victim has been accompanied by the Public Prosecutor during the trial process, but what the Public Prosecutor does is never demands that the defendant provide restitution or material or immaterial compensation. to the victim and the discovery of the victim's rights, currently represented by the prosecutor so that the advocate has not played a role in fulfilling the victim's rights, so the advocate has not been able to uphold the victim's rights in the criminal justice process in this case the victim is represented by the prosecutor while the advocate represents the defendant and the Role of the Advocate in fulfilling the rights of victims in the criminal justice system in the future from the perspective of criminal law reform, namely criminal law reform including legal substance, legal structure and legal culture as in Law Number 18 of 2003 concerning Advocates, it is expressly stated that Advocates are law enforcers who have the same position as other law enforcers, such as Judges, Prosecutors and Police as well as future criminal law reforms, advocates can play a role in fulfilling the rights of victims represented by advocates in the criminal justice process starting from the reporting stage to providing restitution or compensation. material and immaterial losses to the victim.